Formulation and Evaluation of Sustained Release Sumatriptan Mucoadhesive Intranasal in-Situ Gel - hussein K. alkufi; Hanan J. Kassab (College of Pharmacy University of Baghdad, 2019)
Objective: The purpose of this study to develop and optimize nasal mucoadhesive in situ gel IG of sumatriptan ST (serotonin agonist) to enhance nasal residence time for migraine management.      Method: Cold method was used to prepare ST nasal in-situ gel, using thermosensitive polymers (poloxamer 407  and/or poloxamer 188) with a mucoadhesive polymer (hyaluronic acid HA) which were examined for gelation temperature and gelation time, pH, drug content, gel strength, spreadability, mucoadhesive force determination, viscosity,  in-vitro drug release, and the selected formula was subjected to ex-vivo permeation study and histological evaluation of the sheep mucosal tissue after application.     Results: The results showed that the formula IG7 prepared from poloxamer 407(19%), poloxamer188 (4%) and HA (0.5%)   had an optimum gelation temperature (32.66±1.52°C), gel  strength (43.66± 1.52 sec),  mucoadhesive force (8067.93± 746.45dyne\cm2), in-vitro drug release (95.98%) over 6hr, ex-vivo permeation study release (89.6%)  during the 6 h. study with no  histological or pathological change in the nasal sheep tissue.     Conclusion: The ease of administration via a nasal drop of ST coupled with less frequent administration and prolong drug release, will enhance patient compliance.